2007
DOI: 10.1038/sj.bjc.6604113
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate, vinblastine, doxorubicin and cisplatin combination regimen as salvage chemotherapy for patients with advanced or metastatic transitional cell carcinoma after failure of gemcitabine and cisplatin chemotherapy

Abstract: We investigated the safety and efficacy of a methotrexate, vinblastine, doxorubicin and cisplatin (M-VAC) combination regimen as second-line chemotherapy for patients with advanced or metastatic transitional cell carcinoma who failed first-line gemcitabine and cisplatin (GC) chemotherapy. Thirty patients who had progressed or relapsed after GC chemotherapy as first-line treatment were enrolled in this study. The major toxicities were neutropaenia and thrombocytopaenia. A grade 3 or 4 neutropaenia occurred in 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 29 publications
2
28
0
Order By: Relevance
“…Various single agents and combinations of agents have been reported as second-line chemotherapy regimens (16)(17)(18)(19)(20)(21)(22)(23). Even in the NCCN guidelines, the second-line chemotherapy data are highly variable and unclear in this setting; thus, no standard therapy exists.…”
Section: Discussionmentioning
confidence: 99%
“…Various single agents and combinations of agents have been reported as second-line chemotherapy regimens (16)(17)(18)(19)(20)(21)(22)(23). Even in the NCCN guidelines, the second-line chemotherapy data are highly variable and unclear in this setting; thus, no standard therapy exists.…”
Section: Discussionmentioning
confidence: 99%
“…In patients progressing on gc or relapsing within 6 to 12 months and still eligible for cisplatin therapy, recent data have shown that a second-line regimen of mvac can offer acceptable outcomes, with an or of 30% and a mds of 10.9 months 87 . The most extensively studied second-line combination regimen is paclitaxel and gemcitabine.…”
Section: Multi-agent Second-line Therapymentioning
confidence: 99%
“…For previous chemotherapy, 18 patients received the GC regimen as the first-line and the M-VAC regimen as the second-line treatments, and three patients received M-VAC as the first-line and GC as the second-line treatments. The median treatment-free interval was 3.5 months (range [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The response rate including complete remission (CR) and PR of the previous two regimens was 38.1%.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…For GC and M-VAC chemotherapy, the specific dose and schedules were the same as in previous reports. 8 For GC chemotherapy, gemcitabine was given at a dose of 1000 mg/m 2 on days 1, 8 and 15, and cisplatin was given at a dose of 70 mg/m 2 on days 2. For M-VAC chemotherapy, the patients received methotrexate 30 mg/m 2 on days 1, 15 and 22; vinblastine 3 mg/m 2 on days 2, 15 and 22; doxorubicin 30 mg/m 2 on day 2; and cisplatin 70 mg/m 2 on day 2.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation